Carbon-isotope stratigraphy of the Middle–Upper Cambrian in eastern Laurentia: Implications for global correlation. (June 2021) - Shembilu, Noel; Azmy, Karem
Abstract: The examined interval of the March Point and Petit Jardin formations (total thickness ~130 m) spans the Middle−Upper Cambrian (lower Port au Port Group) at the Belle Isle Strait, western Newfoundland. The deposits consist of dolomitized shallow-water carbonates ranging from microbial mudstones to oolitic grainstones. A multi-technique evaluation proved the petrographic and geochemical preservation of the investigated micritic carbonates. The δ 13 C and δ 18 O values (−1.2 ± 1.1‰ VPDB and −6.7 ± 1.3‰ VPDB, respectively) exhibit an insigniﬁcant correlation (R 2  = 0.16) and similarly the δ 13 C values with their Mn/Sr ratio (R 2  = 0.01). This supports the preservation of at least near-primary δ 13 C signatures that can be utilized to construct a high-resolution δ 13 C proﬁle for reliable global correlations. The δ 13 C profile exhibits two major negative excursions, the lower excursion (~4‰) immediately below the lower boundary of the March Point Formation (Hawke Bay/March Point boundary) and the upper excursion (~2‰) almost at the lower boundary of the Petit Jardin Formation where these excursions are likely associated with short-term sealevel changes. The trilobite biozonation scheme suggests the correlation of the lower excursion with the DICE (Drumian Carbon Isotope Excursion) event and the upper excursion with the base of the SPICE (Steptoean Positive Carbon Isotope Excursion) counterpart and both events have been globally documented on different paleocontinents. Highlights: δ 13 C composition of Middle-Upper Cambrian carbonates in eastern Laurentia. Distinct negative δ 13 C excursions correlated with the DICE and base of the SPICE events. A useful C-isotope profile for chemostratigraphic correlations in Laurentia and beyond. The δ 13 C profile is consistent with the trilobite biostratigraphic zonation.